SECTIONAL DENTURE USING A NOVEL IN- BUILT DESIGN OF SPECIAL TRAY IN SCLERODERMA PATIENT- CASE REPORT - Dr. P Sneha; Dr Anand KS; Dr Nishna Pradeep; Dr Angitha K; Dr Kevin Reji K; Dr Nadeem Abdul Rahman (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Limited mouth opening is a common occurrence in prosthodontic practice. It may occur due to, genetic disorders, oral cancers, scleroderma, surgical treatment for neoplasms, burns etc. The prosthetic treatment of such patients presents difficulties in all the stages of rehabilitation. This mainly leads to compromised impression making and prosthesis. This article describes the fabrication of a split  impression tray to make a secondary impression and fabrication of sectional denture using press button on edentulous ridge in patient having scleroderma.